Pengaruh Karakteristik Individu, Stres Kerja, Kepercayaan Organisasional terhadap Intention To Stay Melalui Kepuasan Kerja dan Komitmen Organisasi (Studi pada Dosen Tetap Yayasan PTS Makassar) - Arifin. S, Zaenal; Troena, Eka Afnan; Thoyib, Armanu; Nimran, Umar (Jurnal Aplikasi Manajemen, 2010)
Research result indicate that there are 7 hypothesis that positively and significantly influenced, and two hypothesis that positively and significantly not related. The hypothesis that positively and significantly influenced are : (1) Individual Characteristic influence to the job satisfaction, (2) organizational beliefs influenced the job satisfaction,(3) individual characteristic influence the organizational commitment, (4) Work stress influence the organizational commitment, (5) job satisfaction influence the organizational commitment, (6) job satisfaction influence the intention to stay, and (7) organizational commitment influence the intention to stay. While the hypothesis that are not positive and significant influence are: (1) work stress influence the job satisfaction, and (2) organizational beliefs influence the organizational commitment.Keywords: Individual characteristic, work stress, organizational belief, job satisfaction, organizational commitment and intention to stay